PENGAPLIKASIAN SOFTWARE MICROSOFT OFFICE DALAM MENINGKATKAN TUGAS AKADEMIK SISWA SMP TARUNA BHAKTI CIBUNG BULANG KAB. BOGOR: PENGAPLIKASIAN SOFTWARE MICROSOFT OFFICE DALAM MENINGKATKAN TUGAS AKADEMIK SISWA SMP TARUNA BHAKTI CIBUNG BULANG KAB. BOGOR - Purnomo, Bram; Muhajir, Abdullah; Santoso, Muhamad (PT Triputra Sejahtera Prima, 2025)
In the digital era, the field of computer technology, especially Microsoft Office applications, is a basic skill that students must master to meet the demands of the business world. Microsoft Office, including Word, Excel, and PowerPoint, not only increases productivity but also helps students adapt to a professional work environment. This Community Service (PKM) aims to determine the use of Microsoft Office applications to support the work practice activities of students at Taruna Bhakti Junior High School (SMP) Bogor Regency. The PKM method used is Presentation, discussion, and direct practice carried out at the SMP School. The results of the skills show that students are able to understand the basic concepts of using Microsoft Word for information, Excel for data processing, and Power Point for visual presentations. However, limited training time is a major obstacle in achieving optimal results. This study highlights the importance of mastering Microsoft Office as part of a comprehensive professional learning plan to improve students' abilities both in academics and in the workplace in the future. The results of this PKM are expected to be a guideline for Taruna Bhakti Junior High School, especially students, to be more active in learning computers, especially Microsoft Office.